Henrik Madsen: Spies - Et eventyr. (Børsen Bøger. 1994). 242 s., 248 kr. Jan Cortzen: Myten Møller. Mærsk Mc- Kinney Møller - han gør Danmark rigere. (Børsen Bøger, 1994) 353 s., 98 kr. - Ronit, Karsten (Historie/Jyske Samlinger, 1995)
-